HABITAT AND POPULATION OF MANGROVE CRAB (Scylla serrata) IN MANGROVE FOREST IN TELUK AMBON BAGUALA DISTRICT - Timothy F. Tarumasely; Fanny Soselisa; A. Tuhumury (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
Passo village has mangrove forests with extent about 23,343 ha. The mangrove ecosystem in Baguala Bay, functions to produce various foods needed by mangrove crabs (Scylla serrata) in the form of organic materials and other types of natural feed. The population of mangrove crab (Scylla serrata) in Teluk Ambon Baguala District is so potential but has not been supported by adequate data base. The method used in this study is the Capture Mark Release Recapture (CMRR) method. Mangrove crab abundance were obtained in the first catch of 30 individuals and in the second capture of 31 individuals with an estimated population of 63 indivdu with an upper class limit of 81 individuals and a lower class limit of 48 individuals. Encounters with mangrove crabs are strongly influenced by their habitat, generally in places with dense mangrove vegetation, soft substrates, and are affected by sea tides.